Crystallization and near-infrared emission from host–guest based supramolecular polymers. (28th May 2021) - Yin, Wenxia; Meng, Lingyi; Yu, Tianjun; Chen, Jinping; Hu, Rui; Yang, Guoqiang; Zeng, Yi; Li, Yi
Abstract : Crystallization process of a NIR emissive supramolecular polymer formed by host–guest complexation of a distyrylanthracene derivative and cucurbiturils is described. Abstract : A supramolecular polymer has been prepared by sequential assembly of a distyrylanthracene derivative monomer with CB[7] and CB[8], which exhibits enhanced near infrared emission in the solid state on account of aggregation induced emission and noncovalent isolation effects. The supramolecular polymer forms spherulite layers followed by surface nucleation and 2D growth, and eventually constructs pyramidal crystalline aggregates with a size of about 500 nm. The preliminary study presents the supramolecular polymers crystallization behavior which relates to the aggregation states and functionalities of polymeric supramolecular materials and is worth further investigation both in theory and experiments.